Spirituality/religiosity and cardiovascular system - Valente, Vitor Engrácia [UNESP] (2014)
Introduction: Spirituality/religiosity is associated to well-being. In this article, we describe the association between spirituality/religiosity and cardiovascular system. Materials and methods: We performed searches using Medline, SciELO, Lilacs and Cochrane databases using crossing between the keywords “spirituality,” “cardiovascular system,” “parasympathetic nervous system,” and “sympathetic nervous system.”Results: The electronic search yielded 65 references by crossing the terms “spirituality” and “cardiovascular system.” Among these, the first round of elimination resulted in exclusion of 55 titles and abstracts that were not clearly related to the subject of the review. The titles of the remaining 10 abstracts were submitted to a final evaluation that accounted for the inclusion criteria. An investigation into the reference lists confirmed the absence of relevant documents. Summaries of the analysed studies were selected. Discussion: Among 10 studies selected, 8 of them indicated that spirituality/religiosity is very important for the cardiovascular system, whereas only 2 found no significant association between the two variables in women. Conclusion: We suggest that spirituality/religiosity is an alternative and non-pharmacological therapy for cardiovascular disorders.